Representasi Muslim Modern Timur Tengah dalam Videoklip ‘Stereotype World: The Middle East Speak UP!’ - Alan Surya; Reni Pebriyani (Jurnal Komunikasi Islam, 2022)
This study aims to analyse the representation of Middle Eastern Muslims in the video clip, Stereotype World: The Middle East Speak UP!, created by Haifa Beseisso, a rapper, Youtube vlogger, philanthropist and Palestinian activist in collaboration with Qatari director Kimo Basha. Using Roland Barthes' Semiotics analysis, the findings illustrate that the visual codes in the video clip Stereotype World: The Middle East Speak UP! deconstruct Middle Eastern myths built by Orientalists. This video clip represents modern-civilised Middle Eastern Muslims, friendly people who love peace and respect differences. Additionally, Islam, which is depicted through Muslim Tengah in this video clip, represents freedom of expression for Muslim women with advanced civilization and a modern lifestyle.